Poetry and Suffering of the Psyche: A Hermeneutic Literature Review of the Works of the Poet Yun Dong-ju - Yoo, Elie Sinyoung (Auckland University of Technology, 2023)
In this dissertation, I explore the relationship between poetry as an art form and the human experience of psychological suffering through closely examining the works of Korean poet Yun Dong-ju. Many ancient cultures associate poetry with medicine and healing. In the modern world, poetry is recognised as a valuable tool for therapeutic purposes and is utilised by various mental health professions. A hermeneutic methodology guides the conduct of a nuanced hermeneutic literature review in which I focus on Yun Dong-ju's poetry, prose, and related literature discussing his life and work. Through this review, I explore various facets of poetry. The review reveals several functions of poetry in relation to Yun Dong-ju's psychological suffering. One significant function, referred to as 'personal myth,' involves the use of 'poetic language,' consisting of metaphors, analogies, and symbols. For Yun Dong-ju, poetry serves as a means to explore and construct his inner narrative about self. This process leads him to a deeper understanding of his internality, fostering psychological growth and a sense of healing. It seems that the construction of his own 'personal myth' nurtures the generation of meaning about his sufferings, enabling him to counter existential crises. Through this review, it is revealed that poetry can provide a safe container, enabling the expression and navigation of nuanced and subjective emotional realities linked to the excruciating sense of psychological suffering. The findings suggest that the core potency of poetry lies in the pursuit of meaning, even in the face of adversity and meaninglessness, and particularly in the context of individual psychological suffering. Furthermore, it is discovered that poetry has the potential to address collective trauma and promote collective healing, bridging divides within individuals with diverse cultural, historical, and ancestral backgrounds. The findings of this research reveal significant potentials for the use of poetry in the fields of psychotherapy and mental health, both for individual trauma and collective/intergenerational trauma within individuals. It is also implied that the effectiveness and potency of poetry in therapy may closely relate to the therapist’s subjectivity, temperament, value systems, and their alignment with the therapist’s creativity and artistic mode of being. Thus, the therapist’s own subjectivity can function as a poetic presence, even without the explicit use of poetry in therapy. Furthermore, poetry may help bridge cultural gaps in multicultural contexts, like Aotearoa New Zealand, by enabling nuanced understandings of individual emotions and fostering a sense of cultural safety. Overall, what is revealed is that for the practice of psychotherapy, poetry can facilitate nuanced emotional attunement between therapist and client.